2020
DOI: 10.3389/fchem.2020.617448
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Antimalarial, Antitrypanosomal, and Antileishmanial Activities of Natural Compounds Isolated From Nigerian Flora

Abstract: The West African country Nigeria features highly diverse vegetation and climatic conditions that range from rain forest bordering the Atlantic Ocean in the South to the Desert (Sahara) at the Northern extreme. Based on data from the World Conservation Monitoring Center of the United Nations Environmental Protection, Nigeria, with ~5,000 documented vascular plants, ranks amongst the top 50 countries in terms of biodiversity. Such a rich biodiversity implies that the country is rich in diverse secondary metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 107 publications
2
25
0
Order By: Relevance
“…Flavonoids have been found to have antimalarial effects via reducing hemoglobin breakdown by blocking the action of the cysteine protease enzyme falcipain-2 [3]. The saponins also have an antimalarial impact by damaging the cell membranes of infected erythrocytes, causing erythrocyte cells to lyse [23], [24]. Alkaloids have been proven to reduce parasitemia levels by suppressing parasite DNA and RNA production 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids have been found to have antimalarial effects via reducing hemoglobin breakdown by blocking the action of the cysteine protease enzyme falcipain-2 [3]. The saponins also have an antimalarial impact by damaging the cell membranes of infected erythrocytes, causing erythrocyte cells to lyse [23], [24]. Alkaloids have been proven to reduce parasitemia levels by suppressing parasite DNA and RNA production 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Since nearly 80% of people rely on traditional medicine, plants and plant products have been used in the treatment of diseases for many centuries before the active principles in these products could be elucidated. About 50% of prescribed drugs are either plant-produced or their derivatives (Ungogo et al, 2020). Combination therapy using medicinal plants has effectiveness against a number of viruses, including herpes and influenza viruses.…”
Section: Source Of Antiviral Agentsmentioning
confidence: 99%
“…Over the last decade, several reviews have reported the bioactivity of natural products against protozoan neglected diseases [ 7 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. However, natural products described in these reviews were obtained from different sources, including microbial [ 19 ], endophytes [ 20 ] and other fungi [ 21 ], marine [ 22 ], or animal origins [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some reviews also present a mix of natural compounds origins [ 7 , 17 ]. Regarding natural products from plants, since 2016, there have been some reviews focusing exclusively on compounds from higher plants [ 16 , 18 , 25 , 26 , 27 , 28 , 29 , 30 ]. Nevertheless, the information is scattered amongst the diverse antiprotozoal diseases, compound families, and sources.…”
Section: Introductionmentioning
confidence: 99%